Analisis Efektivitas dan Kontribusi Pajak Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) Terhadap Pendapatan Asli Daerah - Muh Fachrul Firdaus; Nur Afiah; Masdar Ryketeng (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study aims to analyze the effectiveness and contribution of the Land and Building Rights Acquisition Tax (BPHTB) to the Locally-Generated Revenue (PAD) of Barru Regency. The data collection technique used is documentation. This study employs a quantitative method with an analysis of the effectiveness ratio and contribution ratio. This study uses primary data which includes regional tax revenue reports for the 2021-2023 period. The results indicate that the collection effectiveness of the Land and Building Rights Acquisition Tax (BPHTB) in Barru Regency during 2021-2023 is still considered effective, with an average effectiveness rate of 92.98%. However, the contribution of BPHTB to Locally-Generated Revenue (PAD) remains very low with an average rate 3,36%.